(untitled) (Research, Society and Development, 2021)
Bacterial urinary tract infections (UTI) are among the most frequent infectious diseases of small animals. Although antimicrobial therapy is recommended for treating bacterial UTIs, the current consensus is that treatment may not be necessary for asymptomatic animals. The aim of this study was to evaluate the diagnostic ability of urinalysis to detect bacteriuria and to compare it with urine culture (gold standard method) to assess the risk of false-positive results. A retrospective study was conducted from January 2016 to July 2019 and urine samples of 119 dogs were analyzed. Diagnostic validation was performed for urinalysis, based on the morphological classification and intensity of bacteriuria. Agreement between the results was assessed using the kappa (k) index. When the presence of cocci was used as a diagnostic criterion to suggest bacteriuria, it was observed that the agreement (k = -0.006) was lower than that expected by chance. However, a poor agreement (k = 0.22) was also found for bacilli during urinalysis (k = 0.23). A significant degree of agreement was observed in cases with high intensity of bacteriuria. Therefore, urine culture must be performed for conclusive evidence of bacteriuria to avoid false-positive results during urinalysis.